Pan-Cancer Analysis of Histone Methyltransferase KMT2D with Potential Implications for Prognosis and Immunotherapy in Human Cancer - Chen, Guoning; Chen, Peijie; Zhou, Jianwen; Luo, Guangcheng (Combinatorial Chemistry & High Throughput Screening, 2023)
Background: Pan-cancer analysis is an efficient tool to obtain a panoramic view of cancer- related genes and identify their oncogenic processes, facilitating the development of new therapeutic targets. Lysine methyltransferase 2D (KMT2D), acting as a major enhancer coactivator for mammalian cells, is one of the most frequently mutated genes across various cancer types and is considered an oncogene and a rationale for epigenetic therapeutic targets. Objective: This study was designed to explore the potential role of KMT2D in human cancer through a pan-cancer analysis. Methods: The expression of KMT2D was assessed in normal tissues and cell lines, and pancancers from The Cancer Genome Atlas (TCGA), Cancer Cell Line Encyclopedia (CCLE), and Genotype-Tissue Expression (GTE) datasets were used to explore its correlation with prognosis, immune cell infiltration, tumor mutation burden, microsatellite instability, and mismatch repair. Results: KMT2D expression was heterogeneous across different cancer types. Increased KMT2D indicated a worse prognosis in adrenocortical carcinoma (ACC), brain lower-grade glioma (LGG), and mesothelioma (MESO), while patients with high KMT2D expression showed better outcomes in renal clear cell carcinoma (KIRC). Moreover, KMT2D expression was positively correlated with immune cell infiltration and negative tumor mutation burden in multiple cancers. In addition, a significant correlation between KMT2D and immune checkpoint-related genes or mismatch repair genes was identified. Conclusions: These findings support the hypothesis that KMT2D is not only a potential biomarker for prognosis and immunotherapy response prediction but also an essential immune regulator in human cancer.
Keywords: immunotherapy